IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENGEMBANGKAN SEKOLAH ADIWIYATA MANDIRI DI UPTD SD NEGERI KECAMATAN PAMULANG - Ernawati, Neneng; Masriah, Imas; Utaminingsih, Sri (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the implementation of School-Based Management in developing the Adiwiyata Mandiri Program at UPTD SD Negeri Kecamatan Pamulang as an effort to strengthen environmental education in elementary schools. The research employed a descriptive qualitative approach through in-depth interviews, participatory observations, and document analysis to obtain a comprehensive overview of the planning, organizing, implementation, and monitoring of the Adiwiyata program. Data were analyzed using an interactive model that includes data reduction, data display, and conclusion drawing. The results indicate that the implementation of School-Based Management follows a systematic and participatory process, characterized by planning that involves all school stakeholders, clear task division within the Adiwiyata Team, integration of environmental values into learning activities, and monitoring supported by digital documentation. Key supporting factors include strong school leadership, teacher commitment, student participation, and support from the school committee, while the main challenges involve limited funding, insufficient teacher training, and low environmental awareness among some parents. The novelty of this study lies in its comprehensive mapping of the relationship between SBM dimensions and the effectiveness of the Adiwiyata Mandiri program, offering an implementation model that can be replicated by other elementary schools.